Annex 1. A. Common terminologies in pasture and forage science. B. Tropical pasture and forage species in the subhumid zone - Otsyina, R.M.; Mohamed-Saleem, M.A. (International Livestock Centre for Africa, 1984)
Defines some of the terms commonly used and misused in forage production and management in relation to farming systems research. Also provides a quick reference of some of the pasture and forage species found in the subhumid zone of Nigeria.